Serum biochemical profile from clinically healthy campeiro horses Perfil bioquímico sérico de equinos clinicamente sadios da raça Campeiro - Souza A.F.* (2016)
Blood samples were obtained from 138 equines of the Campeiro breed with mean ages of 9.7±5.4 years, including 14 males (10.15%) and 124 mares (89.85%). Mean values of serum of GGT: 13.73 ± 4.08U/L; AST: 246.34±72.87U/L; ALT 5.13±1.18U/L; FA: 284.32±53.33IU/L; CK: 132.54±72.25U/L; LDH: 511.38±143.65U/L; and serum urea: 38.65±12.62mg/dL and creatinine: 1.24±0.24mg/dL were observed. The mean values of AST, FA, ALT, urea and creatinine were similar to those proposed in the literature for other breeds. The CK values, GGT, and LDH were higher than those commonly used as references. There was no difference in the concentrations of any of the serum components evaluated at different ages analyzed. Further average values in the lower urea concentrations and creatinine were observed in females compared to males, as well as the higher serum activity of FA in pregnant mares in relation to non-pregnant. Serum biochemical profile of healthy horses of the Campeiro breed presents peculiar variations that must be taken into consideration in the interpretation of laboratory tests.